„Luźne” znaleziska żelaznych grotów oszczepów kultury przeworskiej z Wyżyny Sandomierskiej i jej obrzeża - Florek, Marek (Muzeum Okręgowe w Rzeszowie, 2020)
The subject of the research are 5 spearheads from the villages: Leszczków, Rytwiany, Szczeka and Lubienia, in the Świętokrzyskie voivodeship. The artefacts, apart from the one from Szczeka, were found by accident, probably in the course of illegal searches with the use of metal detectors. The spearheads should be dated to the younger Pre-Roman period and the Roman period. They probably come from the destroyed cremation graves from the unknown so far cemeteries of the Przeworsk culture.

In 2012–2019, the Provincial Heritage Monuments Protection Office in Sandomierz received 5 “stray” finds of iron spearheads of the Przeworsk culture found in the villages: Leszczków, Rytwiany, Szczeka and Lubenia in the Świętokrzyskie voivodeship. The spearhead found in Leszczków most likely belongs to the C type of the 3rd variant of spearheads according to the classification of P. Łuczkiewicz (2006, pp. 105–111) from the younger Pre-Roman period. Two spearheads from Lubenia, probably coming from one grave, are the closest to the M type of spearheads from the younger Roman period. On the other hand, the spearheads from Rytwiany and Szczeka can be classified as type XIX according to the classification of P. Kaczanowski, occurring in phases C1 and C2 of the Roman period. The places where the artefacts were found are located in the Sandomierz Upland and the neighbouring areas of the Połaniec Basin and the Iłża Foothills. Only one spearhead, found in Szczeka, comes from legal, regular searches performed by means of a metal detector. Other relics were probably discovered during illegal searches with the use of a metal detector. In all cases, the finders indicated the place of their discovery, which made it possible to conduct verifying research there. They gave a negative result – no other artefacts were found in the indicated places. Nevertheless, it should be assumed with high probability that all spearheads indicate the existence of cemeteries of the Przeworsk Culture in the places where they were found.
“Stray” finds of iron spearheads of the Przeworsk culture from the Sandomierz Upland and its outskirts
Keywords: spearheads; Przeworsk culture; Pre-Roman period; Roman period; Sandomierz Upland